(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
Myocardial infarction (MI) remains one of the leading causes of morbidity and mortality worldwide. The underlying pathophysiology of MI involves a complex interplay between ischemia, reperfusion injury, inflammation, and oxidative stress. Oxidative stress, characterized by an imbalance between reactive oxygen species (ROS) generation and antioxidant defense mechanisms, plays a crucial role in myocardial cell injury, apoptosis, and subsequent ventricular remodeling. Excessive ROS disrupt cellular membranes, mitochondrial function, and signaling cascades, leading to further ischemic damage. This article reviews current understanding of oxidative stress mechanisms in MI, discusses the clinical biomarkers of oxidative damage, and evaluates pharmacological and non-pharmacological strategies for oxidative stress correction. Advances in antioxidant therapies, mitochondrial-targeted drugs, and gene-based approaches are also explored. Optimizing redox balance represents a promising avenue for improving myocardial recovery and patient outcomes following infarction.